Growth And Adaptation Of Leptospires In Low Protein Medium - Govindan, Balakrishnan; Varadharajan, Meenambigai Timiri; Roy , Parimal (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was undertaken to grow leptospires from high protein (20 per cent BSA) to protein free media (without BSA),which revealed growth at the concentration of 20 per cent to one per cent BSA on the 4th day of incubation. No growth could be observed below one per cent level of BSA. Hence, the leptospires were adapted to grow from high protein (10 per cent) to low protein (upto 0.2 per cent) concentration of BSA. In this adaptation process, growth in low protein medium containing 0.2 per cent BSA was observed to a concentration of >1.4 x 109 organisms / ml by day 10 and 11. Hence, the low protein medium containing 0.2 per cent BSA can be used for growing leptospires for vaccine preparation so as to minimize the adverse effects of protein containing media.